Braille for Physics - Ediyanto Ediyanto; Thalsa Syahda Aqilah (Department of Special Education, 2022)
The demand for learning media for those who have visual impairments in learning physics is growing. Braille letters that cannot accommodate physics equations and symbols are an impediment that must be addressed promptly. The technique that can be used is, of course, to present a new version of current Braille. The Braille form for Physics in this article is still a work in progress. We are eager to collaborate with professionals in physics and Braille. In addition, as a follow-up, we will consider validating and constructing a Braille physics dictionary utilizing 3x3 Braille forms.